Prospective Relationship Between Poor Sleep and Substance‐Related Problems in a National Sample of Adolescents. (16th January 2015) - Wong, Maria M.; Robertson, Gail C.; Dyson, Rachel B.
<x xml:space="preserve">Abstract</x> Background Previous studies showed that poor sleep prospectively predicted alcohol‐related problems and illicit drug use in adolescents and young adults (Wong and Brower, 2012; Wong et al., 2010). However, more work needs to be done to elucidate the nature of these problems. The purpose of this study was to examine whether sleep difficulties and hours of sleep prospectively predicted several serious substance‐related problems, for example, binge drinking, driving under the influence of alcohol, and risky sexual behavior. Methods Study participants were 6, 504 adolescents from the National Longitudinal Study of Adolescent Health. Data were collected from interviews and questionnaires. This study analyzed data from the first 3 waves of data (T1: 1994 to 1995; T2: 1996; T3: 2001 to 2002). In all analyses, we used sleep difficulties at a previous wave to predict substance‐related problems at a subsequent wave, while controlling for substance‐related problems at a previous wave. Results Holding T1 alcohol‐related problems constant, sleep difficulties at T1 significantly predicted alcohol‐related interpersonal problems, binge drinking, gotten drunk or very high on alcohol, driving under the influence of alcohol, getting into a sexual situation one later regretted due to drinking, ever using any illicit drugs, and drug‐related problems at T2. T1 hours of sleep negatively predicted T2 alcohol‐related interpersonal problems and binge drinking. The relationship between T2 sleep variables and T3 substance‐related problems was consistent with previous waves, although the effect was weaker. Conclusions Sleep difficulties and hours of sleep are a significant predictor of a number of substance‐related problems. It may be useful to educate adolescents about the importance of sleep, sleep hygiene, and the potential consequences of poor sleep on drinking and related behaviors.